DETERMINANTS OF THE RUSSIAN LABOR MARKET MODEL - Reznikova, Olga; Ganieva, Albina; Verna, Veronica; Korolenko, Julia; Shelygov, Aleksandr (Revista Inclusiones, 2020)
The article is devoted to the determinants of the Russian labor market model. In general, analyzing the Russian labor market model, one can note the flexibility of its structure, as well as the dynamism of its development and formation. Distinctive features of the Russian labor market are described in comparison with the most popular models: American, Japanese, and Swedish. It is proved that the Russian model has features of all analyzed models. Like the American model, it is characterized by high territorial mobility and a fairly high unemployment rate.